2021
DOI: 10.1183/23120541.00027-2021
|View full text |Cite
|
Sign up to set email alerts
|

Delivered dose with jet and mesh nebulisers during spontaneous breathing, noninvasive ventilation and mechanical ventilation using adult lung models

Abstract: What is the delivered dose with jet (JN) and mesh nebulizers (MN) during spontaneous breathing (SB), noninvasive ventilation (NIV), and mechanical ventilation (MV) using an adult lung model with exhaled humidity (EH)? Albuterol sulfate (2.5 mg·3 mL−1) delivery with JN (Mistymax10) and MN (AerogenSolo) was compared during SB, NIV, and MV using breathing parameters (Vt=450 mL, RR=20 bpm, I:E=1:3) with three lung models simulating EH. A manikin was attached to a sinusoidal pump via a filter at the bronchi to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
1
7
0
9
Order By: Relevance
“…This study shows that aerosol delivery to a simulated adult patient during mechanical ventilation is influenced by the type of aerosol drug delivery device selected, with the VMN delivering the highest drug dose across all testing conducted (see Figures 4, 5 and 6). These findings are in agreement with previous works by Ari and Fink (2021) [28], who reported a drug delivery of 23% from the VMN compared to just 7% for a JN during mechanical ventilation with active humidification. One study showed that the use of a VMN in the emergency department (ED) resulted in a reduction in hospital admissions, length of stay in the ED and albuterol drug dose when compared to a JN [29].…”
Section: Effect Of Device Type On Drug Deliverysupporting
confidence: 94%
“…This study shows that aerosol delivery to a simulated adult patient during mechanical ventilation is influenced by the type of aerosol drug delivery device selected, with the VMN delivering the highest drug dose across all testing conducted (see Figures 4, 5 and 6). These findings are in agreement with previous works by Ari and Fink (2021) [28], who reported a drug delivery of 23% from the VMN compared to just 7% for a JN during mechanical ventilation with active humidification. One study showed that the use of a VMN in the emergency department (ED) resulted in a reduction in hospital admissions, length of stay in the ED and albuterol drug dose when compared to a JN [29].…”
Section: Effect Of Device Type On Drug Deliverysupporting
confidence: 94%
“…They may require dilution with normal saline to allow an adequate nebulization rate. Whereas clinical studies with mesh nebulizers during transnasal aerosol delivery to children are limited, in vitro studies showed higher lung deposition with mesh nebulizers than jet nebulizers in this patient population (Ari, 2019;Ari and Fink, 2021).…”
Section: Advantages Disadvantagesmentioning
confidence: 84%
“…Previous in vitro studies on transpulmonary aerosol drug delivery used various lung models, including either nasal cavities or teaching manikins with anatomical airways to emulate the breathing patterns of preterm babies, infants, and children (Bhashyam et al, 2008;Ari et al, 2011;Sunbul et al, 2015;Alalwan et al, 2019;Li et al, 2019a;Li et al, 2019b;Li et al, 2020;Ari and Fink, 2021;Corcoran, 2021;Bass et al, 2022). It should be noted that particle size exiting the nasal prongs is consistently less than 2.6 microns, independent of prong size or gas flow.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…[18,19] They aerosolise solutions via a rapidly vibrating piezo element [20] and their clinical superiority over conventional jet nebulisers (JN) has been demonstrated in multiple studies. [21][22][23][24] VMN also have multiple practical advantages over JN and ultrasonic nebulisers, such as faster treatment times, lower residual volumes and in-line usage and are widely regarded as the future of nebulisation. [19,25] VMN may offer a more effective route for the administration of nebulised normal saline in critical care secretion management compared to traditional JN.…”
Section: Introductionmentioning
confidence: 99%